Improving The Regional Economy by Promoting Branding in Local SMEs - Meriam Esterina; Nenden Nur Annisa; Aby Wahyu Ramadhani (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
SMEs have a big role in supporting the regional economy. Many efforts have been made by all parties, both the central and regional governments so that SMEs can continue to grow. SMEs practitioners in Kalimiru Village, Purworejo, are still limited in number and the average age of them are old. They do not know about the importance of branding and the logo used. The aims of this community service program are to be able to develop the local economy of the local area by empowering home-based businesses to become productive local SMEs. Effective training and socialization of branding and logo design were provided to the people of Kalimiru village to optimize their home industry. Branding and logo design training was given to 20 people Kalimiru Village SMEs. The selected participants already had their own products. Participants are given knowledge about branding in language that is easy to understand so that it is easier to be accepted. Participants were also introduced with making logo designs and media that can be used. The results of this community service program are participants have understood the importance of branding and the media to create their creative logos to support the marketing of their products. Through strong branding and an effective logo, it is hoped that SMEs can be more advanced and support the improvement of the regional economy.